Steroid-Responsive Encephalopathy Associated with Thyroiditis (SREAT): A Case Report of Saving a Young Female Life - Abdelrahman Mahmoud Senosy (Dubai Medical Journal)
Hashimoto’s encephalopathy (HE), a rare autoimmune disorder associated with thyroiditis, is a condition with no definitive cause. Symptoms include altered mental status, seizures, and cognitive impairment. When diagnostic criteria are met, steroids are the cornerstone of treatment with a reported good response. This report presents a 26-year-old female with HE who presented with persistent status epilepticus and altered mental status, complicated by aspiration pneumonia and laryngeal edema, and had been managed successfully. After exclusion of the common causes of acute altered mental status and seizures, early workup for treatable rare causes such as HE can help rapid recovery and avoid complications. However, proper management of complications such as lower respiratory tract infection, if happened, is necessary for good outcome.